Training on Using Canva Application for High School Teachers at Darussilmi Islamic Boarding School in Bintan Regency - Ediyansyah; Setyaningsih, Dwi; Zulhamdan; Perwira, Wanda Gema; Nevianti, Devi Rizka Ayu (Unram Journal of Community Service, 2025)
In this increasingly digital era, learning media have expanded to the use of digital-based technology. The purpose of this community service activity is to enhance teachers' competencies in developing digital learning media using the Canva application. This activity employed the participatory action research method, conducted collaboratively within a community environment with the spirit of encouraging transformative actions toward positive change. The results of this program indicate that 79% of the participating teachers responded positively to the Canva training. Specifically, 79% of teachers strongly agreed that Canva facilitates the creation of learning media; 79% strongly agreed that Canva offers more interesting and user-friendly features; 79% strongly agreed that they are interested in exploring Canva's features more deeply; 77% strongly agreed that the media designed using Canva would be well-liked by students; 77% strongly agreed that Canva’s templates ease the process of creating learning media; and 81% strongly agreed that Canva has improved the quality of their learning media in terms of visual appeal and design.